ANALISIS PENDAPATAN USAHATANI PADI DAN SISTEM PEMASARAN BERAS DI KABUPATEN KARAWANG, PROVINSI JAWA BARAT - Ariyono, Ardie; Nurmalina, rita; Harmini, Harmini (Forum Agribisnis, 2013)
The objectives of this research were to analyses the rice farming income and the rice marketing system in Karawang district. Primary data were collected in this research involvedÂ  34 paddy farmers in Karawang and 12 rice traders and secondary data that is relevant to the research were collected. Â The analysis of rice farming was conducted for the first growing season of 2011. Most of rice farmers are the selfowner with an area of ââbetween 1 to 5 acres. The selling price of unhusked rice crop received by farmers ranged between Rp 2.200,00 to Rp 3.800,00 with an average of Rp 2.720,54. Value of R / C ratio is 1.50 based on total cost. The actors in rice marketing are paddy farmers, local rice mill, sub-districtâs and Cipinangâs market wholesaler and retailer.Â Â  The biggest margin obtained by the local rice mill.Â  The biggest farmerâs share found at the market flows from farmer Ã  sub-district wholesaler Ã  Karawang retailer.Â  The biggest benefit cost ratio of marketing found at market flow from farmers Ã  local rice mill Ã  Cipinang wholesaler Ã  Jabodetabekâs retailer.Â  The market structure at farmer level is nearly perfect, however at the other level (rice mill, wholesaler and retailer) the market structure is oligopoly and oligopsony.Â  The selling price of grain has a significant impact on farmers income, so the role of the Government is expected to overcome this, such as by optimizing the role of the âLumbung Desa Modernâ (LDM), which is the existence still not optimal yet.